Sociedad y justicia penal en Morelia (1892-1911) - Aragón Zavala, Francisco Gerardo (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The restlessness of carrying out a work about the crime rate obeys, in the first place, to a personal interest that arises assisting my formation like lawyer; also, I consider that inside any historical time it is of supreme importance the aspect of the penal justice, since somehow it is a parameter to measure the civilization grade reached by a human group and the level of well-being of the societies. He/she understands each other for crime rate, the desajuste of the behavior of the individuals regarding the norms of social coexistence, and for penal justice, the punishment of those noxious behaviors, for the protection of the collective. It is common that as much the matters as the State, manifest their concern because it exists a decrease or a control of the crime rate, and in a same way because the administration of justice is the most appropriate. The frequency of the criminal acts has always been related to diverse factors like the physical characteristics of the individuals, the intoxication, the alcoholism, its family situation, acquired formation, education level, access to the social generated wealth, politicians specify of the government, control means to combat her, etc.. In that sense, the phenomenon of the crime rate has particularities in each time and in geographical certain spaces. With the result that in the present investigation the study of a certain space is outlined as it is the district of Morelia, and an impermanence that coincides with that that commonly is known as Porfiriato, and that for the case of Michoacán it occupies one period that he/she goes from 1892 to 1911.

La inquietud de realizar un trabajo sobre la criminalidad obedece, en primer lugar, a un interés personal que surge atendiendo a mi formación como abogado; asimismo, considero que dentro de cualquier época histórica es de suma importancia el aspecto de la justicia penal, ya que de alguna manera es un parámetro para medir el grado de civilización alcanzado por un grupo humano y el nivel de bienestar de las sociedades. Se entiende por criminalidad, el desajuste de la conducta de los individuos respecto a las normas de convivencia social, y por justicia penal, el castigo de esas conductas nocivas, para la protección de la colectividad. Es común que tanto los particulares como el Estado, manifiesten su preocupación porque exista una disminución o un control de la criminalidad, y de igual manera porque la administración de justicia sea la más adecuada. La frecuencia de los actos delictivos siempre se ha relacionado a diversos factores como las características físicas de los individuos, la embriaguez, el alcoholismo, su situación familiar, formación adquirida, nivel de educación, acceso a la riqueza social generada, políticas especificas del gobierno, medios de control para combatirla, etcétera. En ese sentido, el fenómeno de la criminalidad tiene particularidades en cada época y en espacios geográficos determinados. De ahí que en la presente investigación esté planteado el estudio de un espacio determinado como es el distrito de Morelia, y una temporalidad que coincide con lo que comúnmente se conoce como el Porfiriato, y que para el caso de Michoacán ocupa un periodo que va de 1892 a 1911.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2008-0007; Opción en historia de México; Sociedad; Justicia penal; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2375